MANAJEMEN HUBUNGAN MASYARAKAT DALAM UPAYA PENINGKATAN CITRA SEKOLAH (STUDI KASUS DI SMAI AL-HAMIDIYAH SUNGAI AMBAWANG) - Ramadhan, Abdullah Rizki; Nabila, Hafidlotun; Nur, Muhammad Amin (Jurnal Manajemen Pendidikan, 2025)
The purpose of this study is to determine and describe comprehensively the process of public relations planning in improving the school's image at SMAI Al-Hamidiyah Sungai Ambawang, the implementation of public relations activities in supporting the school's image, the evaluation of the public relations program as part of the image improvement strategy, and various efforts that have been made by the school in strengthening public relations. This study applies a qualitative approach with a case study research type. Data validity was carried out through the application of four main indicators, namely credibility, transferability, dependability, and confirmability. The results of the study indicate thatFirst All school administrators were involved in the public relations planning process at SMAI Al-Hamidiyah Sungai Ambawang. Planning was carried out systematically and in detail through an annual meeting that outlined the entire public relations program agenda. Second Public relations activities are carried out according to plan, where public relations has the main task of conveying information about all school activities to the community. Third Program evaluation refers to school service standards and is carried out routinely by internal and external parties Fourth Public relations improvement efforts are focused on increasing access to information for the public through updating existing media such as website school.